RESISTENSI TENAGA KESEHATAN TERHADAP IMPLEMENTASI REKAM MEDIS ELEKTRONIK - Joanie DewiJanti Dhartono; G. Agung Krisna Yudha; Purwadhi Purwadhi; Yani Restiani Widjaja (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2026)
Electronic Medical Records (EMR)constitute a strategic infrastructure in the digital transformation of healthcare services. Although they offer improvements in quality, efficiency, and patient safety, EMR implementation often encounters significant resistance from healthcare professionals. This resistance is not merely a technical barrier, but rather a strategic failure that threatens return on investment and the sustainability of digital transformation initiatives. This study employs a systematic literature review with a narrative (meta-synthesis) approach. A total of 10 internationally reputable scientific articles published between 2019 and 2024 were critically analyzed. The articles were sourced from the Scopus, PubMed, and ScienceDirect databases. Thematic synthesis was used to categorize resistance factors and intervention strategies. The findings indicate that healthcare professionals’ resistance is multidimensional, encompassing: (1) disruption of workflow and clinical autonomy; (2) cognitive burden and non–user-centered system design; (3) ethical and data security concerns; and (4) inadequate digital competencies and support systems. From a strategic perspective, this resistance leads to decreased productivity, increased turnover, patient safety risks, and stagnation of innovation. Effective interventions include transformational leadership, early user involvement, structured change management, and incentive alignment.Resistance to EMR represents a strategic management issue that requires an integrated sociotechnical approach. The success of EMR implementation is not determined by technological sophistication, but by the organization’s ability to manage human factors and change processes. Further evidence-based intervention research is needed within the Indonesian healthcare context